Post-exercise heart rate recovery and its speed are associated with cardiac autonomic responsiveness following orthostatic stress test in men. (30th July 2021) - Molina, Guilherme E.; da Cruz, Carlos J. G.; Fontana, Keila E.; Soares, Edgard M. K. V. K.; Porto, Luiz Guilherme G.; Junqueira, Luiz Fernando
Abstract: Objective: The present study sought to expand upon prior investigations of the relationship between the post-exercise heart rate recovery (HRR) and the cardiac autonomic responsiveness after orthostatic stress test. Method: HRR at the 1st, 3rd, and 5th min after maximal exercise test were correlated with relative change (Δ %) of time-domain (CV, pNN50, and rMSSD) and frequency-domain (TP, LF, HF, and LF/HF ratio) indices of heart rate variability (HRV) after active orthostatic test in 46 healthy men. Statistical analysis employed non-parametric tests with a p-value set at 5%. Results: HRR at 1st min correlated with Δ %pNN50 (rs :0.36 – p  = .02). In the 3rd and 5th min, these measures correlated with Δ %pNN50, Δ %rMSSD, Δ %CV, Δ %TP, and Δ %HF indices (rs :0.33, 0.59 – p  ≤ .05). Coefficient of HRR at the 1st min correlated with Δ %pNN50, Δ %rMSSD, and Δ %HF (rs :0.28, 0.45 – p  ≤ .05). The 3rd and 5th min showed correlation with Δ %pNN50, Δ %rMSSD, Δ %HF, Δ %CV, and Δ %TP (rs :0.37, 0.64 – p  ≤ .05). No correlation was found with indices combined sympathetic-parasympathetic modulation and HRR. After the sample was divided into high and low parasympathetic responsiveness subgroups after the orthostatic test, faster HRR was associated with the degree of parasympathetic responsiveness (reduction) following postural change ( p  ≤ .05). Conclusion: HRR throughout the 1st to 5th min is positively correlated with parasympathetic responsiveness and overall cardiac autonomic modulation of HRV after the orthostatic stress test, and faster HRR is positively correlated with the relative degree of parasympathetic responsiveness after the active postural change at rest in healthy men.